2014
DOI: 10.1590/2317-1545v36n41009
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol and seed transmission of Bipolaris oryzae and Gerlachia oryzae to rice seedlings

Abstract: -Bipolaris oryzae and Gerlachia oryzae, which cause rice brown spot and leaf scald, respectively, are mainly disseminated by seeds. The aim of this study was to evaluate the potential of seeds microbiolization to reduce transmission of these pathogens to seedlings by using the bacteria DFs185 (Pseudomonas synxantha), DFs223 (P. fluorescens), DFs306 (unidentified) and DFs418 (Bacillus sp.). Seeds naturally infested/infected with both pathogens were immersed in suspension of these bacteria (A 540 = 0.5) individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Pseudomonas and Bacillus isolates were reported to control the rice blast fungus P. oryzae (Suryadi, Susilowati, Riana, & Mubarik, 2013). Inoculation with P. fluorescens and Bacillus isolates via seed treatment was effective in controlling the brown spot fungus B. oryzae and the leaf scald fungus G. oryzae in rice (Moura et al, 2014). Another study found that rice seeds inoculated with B. subtilis DFs422 and infected with G. oryzae showed low-severity symptoms of the disease for the first 21 days and became resistant to the fungus after this period (Ludwig, Moura, Santos, & Ribeiro, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas and Bacillus isolates were reported to control the rice blast fungus P. oryzae (Suryadi, Susilowati, Riana, & Mubarik, 2013). Inoculation with P. fluorescens and Bacillus isolates via seed treatment was effective in controlling the brown spot fungus B. oryzae and the leaf scald fungus G. oryzae in rice (Moura et al, 2014). Another study found that rice seeds inoculated with B. subtilis DFs422 and infected with G. oryzae showed low-severity symptoms of the disease for the first 21 days and became resistant to the fungus after this period (Ludwig, Moura, Santos, & Ribeiro, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Those results were very similar to those found in the present study. Moura et al [26] also found that Bacillus spp. inoculated on rice seeds (Oryza sativa L.) was efficient in the control of Gerlachia oryzae, causal agent of scald spot and Silva et al [5] confirmed the potential of B. cereus and Bacillus sp.…”
Section: Fov Seed Transmission To the Seedlingsmentioning
confidence: 95%
“…A significant increase of length and dry matter of seedlings were verified in some studies of seeds treated with Trichoderma spp. [10,11,26,27,28].…”
Section: Effect Of the Biocontrol Agents In The Physiological Qualitymentioning
confidence: 99%
“…was studied and it was cleared that disease severity decreased in rice infected seeds treated with bacteria (Moura et al, 2014).…”
Section: Introductionmentioning
confidence: 99%